IMPLEMENTASI PERATURAN PRESIDEN NOMOR 12 TAHUN 2021 DALAM PELAKSANAAN PENGADAAN BARANG/JASA OLEH PEMERINTAH DAERAH DI PROVINSI SULAWESI UTARA - Fonnyke Pongkorung; Hervian Yulia Rumengan; Rudy M.K. Mamangkey (Fakultas Hukum Universitas Kristen Indonesia, 2026)
The government has established regulations on the procurement of goods/services to avoid problems in their implementation. However, bribery and gratuity practices are often found in the procurement of goods/services during the tender process. This study aims to determine the legal regulations governing the procurement of goods/services in the Regional Government of North Sulawesi and to determine the application of the law in the procurement of goods/services in the Regional Government of North Sulawesi. The research method used is a normative legal research method with a statutory approach and a conceptual approach. In this study, data/legal materials were collected based on literature studies and supported by data collection in the field (empirical research). The collected data were analyzed using qualitative data analysis. The results of the study indicate that the regulation of Government Procurement of Goods/Services is regulated in Presidential Regulation Number 16 of 2018, and then changes were made in Presidential Regulation Number 12 of 2021 concerning the First Amendment to Presidential Regulation Number 16 of 2018 concerning Government Procurement of Goods/Services. The latest development in 2025 saw another change with the enactment of Presidential Regulation Number 46 of 2025 concerning the Second Amendment to Presidential Regulation Number 16 of 2018 and Presidential Regulation No. 12 of 2021 concerning Government Procurement of Goods/Services. The Regional Government, through the PBJ Section and the PBJ Working Group, has implemented the PBJ implementation mechanism in accordance with applicable regulations, however, in practice, violations still occur during the PBJ implementation stages.